The Relationship Between Physical Activity and the Incidence of Non-Communicable Diseases in Indonesia - Rohman Daka; Evi Martha (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction : Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and heart disease have become serious global health problems, with increasing prevalence, especially in developing countries such as Indonesia. NCDs contribute to a large proportion of mortality and morbidity, prompting the need for further research to understand the factors contributing to the incidence of these diseases. Objective : To analyze the relationship between physical activity and NCD incidence in Indonesia based on a collection of journals that have been studied. Methods: This research uses Systematic literature review method with The source of information for the article was done through a search from PubMed, ScienceDirect, and Google Scholar published from 2019 to 2024 obtained 13 articles according to the inclusion criteria. Results: The study showed that people with low levels of physical activity have a higher risk of experiencing NCDs, while sufficient physical activity can significantly reduce the risk of NCDs. Conclusions : There is a significant relationship between physical activity and the incidence of NCDs. The need for a more systematic intervention program including counseling and provision of supporting facilities is expected to reduce the prevalence of NCDs and improve the quality of life of the community